A bathymetric sidescan sonar system - Roy, Stuart (Department of Electrical Engineering, 2016)
The design and construction of a bathymetric sidescan sonar system capable of operation over a 39 degree vertical sector is described. Field tests conducted at a dam site indicate that the completed system does not function as required. This is due to errors in the sonar depth measurement which are caused by reverberation resulting from the multiple scattering of sound from the dam floor. Recommendations are made so that future systems will be less susceptible to this interference source.